Design of a miniaturised broadband 3 × 3 mm antenna for intraocular retinal prosthesis application. Issue 20 (1st October 2018) - Kaim, Vikrant; Kanaujia, Binod K.; Rambabu, Karumudi
Abstract : A highly compact and broadband antenna suitable for a prosthetic device to restore vision in the blind is presented. By embedding three straight sections of meandered microstrip patch line at the feed point, the proposed antenna gives three separate bands at 2.45, 4.2, and 5.8 GHz. The square patch loop is etched in the centre for miniaturisation. Three U‐shaped patch stubs are utilised for frequency tuning. Three bands are merged together by adopting two square annular rings in the ground to obtain a wider bandwidth (2–8 GHz) incorporating unlicensed industrial, scientific and medical (ISM) and UWB bands.